The three levels of theology - Osorio Torres, Juan Alberto (2012)
The text highlights the theology´s role that results from performing the pastoral functioning of a Church or diocese in understanding the need and usefulness of its function. It reiterates not only in the ecclesial function of the theology, but also warms, above all, the testimonial wealth of pastors and the faithful, whose public and profound communion realizes a strong option made by the members of such diocesan community: having decided to subordinatethe weight of the structure and tradition to the urgency of the Gospel and the process undertaken for the Kingdom, despite the conflict and the crisis that it implies. After II Vatican Council and Medellin, the understanding and rationale of the theology not only has the biblical, patristic and kerygmatic level, but also the diocesan level, its best and most attractive historical synthesis experienced